Don't Ask Me If You Will Not Listen: The Dilemma of Consultative Participation - Corgnet, Brice; Hernán González, Roberto (Management Science, 2014)
We study the effect of consultative participation in an experimental principal–agent game, where the principal can consult the agent's preferred option regarding the cost function of the transfer to be implemented in the final stage of the game. We show that consulting the agent was beneficial to principals as long as they followed the agent's choice. Ignoring the agent's choice was detrimental to the principal because it engendered negative emotions and low levels of transfers. Nevertheless, the majority of principals were reluctant to change their mind and adopt the agent's proposal. Our results suggest that the ability to change one's own mind is an important dimension of managerial success. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1786 . This paper was accepted by Teck-Hua Ho, behavioral economics.